Formalising the informal: The ‘fate’ of Village Banks - Bolton, Katy May (Department of Commercial Law, 2019)
As our lives become more and more regulated by the powers that be, it is pertinent that there be acknowledgement of the people that are subject to these rules. When government attempts to regulate aspects of human lives, these regulations exist alongside the embedded mores of communities and the resulting social constructs.1 For this reason, one cannot dismiss the relevance of informal practices when discussing the formal sector and the prospect of regulation of such. With the gradual ‘financialising’ of those previously thought of as ‘unbanked’, there is a steady move toward increased interaction with credit, savings and financial transactions in general.2 Elizabeth Hull notes that as this trajectory continues, there has been a shift in efforts to provide financial services to those who fall outside of the formal sector. 3 The enthusiasm of such efforts has however differed between the informal and formal sector. Formal financial service provision for the poor is still severely lacking, due to the systemic flaws in financial institutions, which include high transaction costs, the need for collateral and stringent regulations.4 As a result of these inadequacies, informal financial services have flourished as they aim to mitigate the flaws associated with the formal sectors, in the hopes of fostering inclusion and pursuing economic sustainability.5 The Village Bank is one such informal financial service. The term ‘Village Bank’ is one widely used in the economic and anthropological literature to describe a member-based bank, usually operating at the intersection of the formal and informal sectors. I will use this terminology throughout my dissertation to reflect the concept as framed in the social science literature. In part 1.4 below, I give further details as to a possible definition of the Village Banks concept.